Variability of total antioxidant capacity among durum wheat genotypes - Taddei F.; Ciccoritti R.; Cacciatori P.; D'Egidio M.G. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Durum wheat (Triticum turgidum L., ssp. durum) contains many health-promoting components involved in different biological activity, partly attributed to potential chemo-preventive substances (phytochemicals), including antioxidants present in high amounts in vegetable crops and also in cereal grains. Recently, the determination of total antioxidant capacity (TAC) has gained a growing interest as a tool for exploring the putative role of antioxidant-rich products in the prevention of degenerative diseases and for the selection of varieties with potentially positive health benefits. The aim of the present study was to determine the influence of the genotype, year and environment on the TAC level in different cultivars of durum wheat during 2009, 2010 and 2011 crop years and in 3 environments. The results showed that year (Y), environment (E) and genotype (G), as well as their interactions, significantly influenced the TAC value in the durum wheat grains. Principal component analysis (PCA) identified genotypes with high and stable TAC values over the environments. Correspondence analysis and boxplots were also useful for assessing more stable cultivars over the years. Among different genotypes, the TAC values ranged between 36,55 to 55,83 mmolTEAC/kg (dry matter, DM).
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)